Studi Hermeneutik: Problematika Teks Henokh 15:7 Terhadap Penggunaannya dalam Matius 22:29-30 - Waruwu, Vanny Miracleson; Kansil, Dicky (STT Saint Paul Bandung, 2023)
The books in the New Testament are specifically mentioned as having references in the Old Testament as their theological basis. However, if you look at the words Jesus in the book of Matthew 22:29-30, it turns out that there is no reference to this theme in the Old Testament, but it refers to the book of Enoch, which is a non-canonical book. This research uses qualitative methods with a pure theological research approach aimed at seeking a deeper understanding of the theological truths contained in the Bible and Christian tradition. The results of the research show that in the search, similarities were found which could then be categorized as identical between the themes in the texts of Matthew 22:29-30 and Enoch 15:7, and the historical hermeneutical problems that occurred as a result of the relationship between the two were seen from the perspective of the book of Enoch as a worthy reference book. to be used as a reference like ordinary books.